2010
DOI: 10.1111/j.1528-1167.2010.02564.x
|View full text |Cite
|
Sign up to set email alerts
|

Vigabatrin‐associated reversible MRI signal changes in patients with infantile spasms

Abstract: SUMMARYPurpose: To evaluate the magnetic resonance imaging (MRI) of pediatric patients with infantile spasms (IS) treated with vigabatrin (VGB) in order to investigate whether VGB affects the brain. Methods: One hundred seven pediatric patients diagnosed with IS and treated with (n = 95) ‡120 mg/kg/day VGB or without (n = 12) VGB were included. MRI and diffusion-weighted imaging (DWI) were retrospectively analyzed. Results: Of the patients who had MRI scans during, but not before, VGB treatment (n = 81), 25 (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 33 publications
5
80
2
Order By: Relevance
“…Previous studies have shown that children younger than 2 years of age were more likely to demonstrate abnormal signal intensity in the deep gray nuclei and dorsal brain stem compared with older children or adults when exposed to vigabatrin. 5,7,16 The observed abnormal signal intensity in the deep gray nuclei and dorsal brain stem in infants with relatively immature myelin exposed to vigabatrin may not be related to myelin vacuolationhence, the lack of significant alteration of D Ќ in the globi pallidi, thalami, and dorsal brain stem in our cohort of patients.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous studies have shown that children younger than 2 years of age were more likely to demonstrate abnormal signal intensity in the deep gray nuclei and dorsal brain stem compared with older children or adults when exposed to vigabatrin. 5,7,16 The observed abnormal signal intensity in the deep gray nuclei and dorsal brain stem in infants with relatively immature myelin exposed to vigabatrin may not be related to myelin vacuolationhence, the lack of significant alteration of D Ќ in the globi pallidi, thalami, and dorsal brain stem in our cohort of patients.…”
Section: Discussionmentioning
confidence: 89%
“…[5][6][7] The underlying microstructural changes responsible for the T2 and diffusion changes in the human brain are unknown. However, on the basis of animal studies, we postulated that the abnormal T2 signal intensity and diffusion restriction in the deep gray nuclei and dorsal brain stem were related to intramyelin edema.…”
Section: -7mentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperintensities in basal ganglia, thalamus, brainstem and dentate nucleus have, very recently, been shown in approximately one-third of those exposed to vigabatrin [76][77][78][79]. These MRI abnormalities may occur as early as 3 months after the initiation of therapy.…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…2 Further studies have described reversibility of MRI defect in infants. 10,11 In 1997, Eke et al reported 3 patients receiving a variety of antiepileptic drugs including vigabatrin showed symptomatic constriction of the visual field. 11 Electroretinogram abnormalities have been identified in these patients with visual field defined toxicity.…”
mentioning
confidence: 99%